Recovery from opioid use disorder: A 4-year post-clinical trial outcomes study. (1st May 2022) - Craft, William H.; Tegge, Allison N.; Keith, Diana R.; Shin, Hwasoo; Williams, Jacob; Athamneh, Liqa N.; Stein, Jeffrey S.; Chilcoat, Howard D.; Le Moigne, Anne; DeVeaugh-Geiss, Angela; Bickel, Warren K.
Abstract: Background: Opioid use disorder (OUD) seriously impacts public health in the United States. However, few investigations of long-term outcomes following treatment with medication for OUD exist. Additionally, these studies have prioritized opioid use and treatment utilization outcomes, and a gap in knowledge regarding long-term, multidimensional trajectories of OUD recovery exists. This study investigated a diverse array of outcomes for individuals with OUD at an average of 4.2 years post clinical trial participation. Methods: Individuals who previously participated in long-acting buprenorphine subcutaneous injection clinical trials (NCT023579011; NCT025100142; NCT02896296) and enrolled in The Remission from Chronic Opioid Use-Studying Environmental and SocioEconomic Factors on Recovery (RECOVER; NCT03604861) Study participated in a follow up assessment (n = 216). Substance use, psychosocial, opioid dependence, and delay discounting outcomes were assessed. Regression analyses were conducted to determine significant associations between psychosocial/opioid dependence variables and both recent opioid use and delay discounting. Results: The majority of participants reported abstinence from opioids since the last RECOVER study assessment (mean 2.26 years; 55%) and in the past 30 days (69%). Participants reported low levels of depression and psychological distress. Positive associations between depression and opioid craving with past 30-day opioid misuse and delay discounting, and negative associations between quality of life and treatment effectiveness with these outcomes were observed. Conclusions: This study examined longer term OUD recovery outcomes. Participants reported high levels of abstinence from opioids and psychosocial functioning. These encouraging results highlight the multidimensional nature of recovery from OUD, and further support the effectiveness of buprenorphine as an OUD treatment. Highlights: Multidimensional outcomes of opioid use disorder (OUD) were studied. High opioid abstinence rates reported at longer term (4.2 years) OUD recovery. High psychosocial functioning reported at longer term OUD recovery. High proportion continued to seek substance use disorder treatment. Delay discounting was associated with psychosocial and opioid use outcomes.